What lies in the woods - Marshall, Kate Alice (New York : Flatiron Books, 2023)
"Twenty-two years ago, Naomi Shaw believed in magic. She and her two best friends, Cassidy and Olivia, spent that summer roaming the woods, imagining a world of ceremony and wonder-the Goddess Game. The summer ended suddenly when Naomi was attacked. Miraculously, she survived her seventeen stab wounds and lived to identify the man who had hurt her. The girls' testimony put away a serial killer, wanted for murdering six women. They were heroes. And they were liars. For decades, the friends have kept a secret worth killing for. But now Olivia wants to tell, and Naomi sets out to find out what really happened in the woods-no matter how dangerous the truth turns out to be."--
Keywords: Missing persons -- Fiction; Secrecy -- Fiction; Truthfulness and falsehood -- Fiction; Serial murderers -- Fiction; Best friends -- Fiction; Thrillers (Fiction)